Test to evaluate the mental representation of technical and dynamic knowledge in pre-established sports actions in taekwondo poomsae/Test para evaluar la representación mental de los conocimientos técnicos y dinámicos en las acciones deportivas preestable - Roberto Fernández Fonseca; Liliana Marìa del Monte del Monte (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: At the Cuban Sports Research Center, studies have been carried out to improve the mental representation of poomsae in high sports performance of taekwondo, related to the logical ordering of its technical sequence. However, it is also necessary to assess the dynamic accents of the movement, which are also evaluated in competition. Objective: The objective of this work was to determine, through a test, the level of knowledge of the technical and dynamic component that the athlete possesses in the mental plane of a pre-established exercises complex such as the world taekwondo poomsae Materials and methods: The empirical methods of documentary review and measurement test were used, as well as the theoretical Inductive-deductive and abstraction methods. Likewise, a formula was assumed to determine the effectiveness of the technical and dynamic ordering of the poomsae, as well as the use of statistical procedures of empirical distributions of frequency with percentage distribution. The population was a study of ten taekwondo specialists, of which subject number eight is presented in a case study. Results: Among the fundamental results, omissions of technical order were identified, but also of important dynamic aspects in the internal model of the studied subject that were not previously detected and, now with this proposal, they can be methodologically treated with greater focus to eradicate them. Conclusions: The theoretical referents on the subject of study supported the analyzes and theoretical inferences expressed by the authors about the theoretical feasibility of the test studied, in which a didactic and methodological enrichment of its content and evaluation was appreciated.